Students’ Perception in Using Social Media as Language Learning - Tri Arie Bowo; Eka Dyah Puspita Sari; Maya Kurnia Dewi (CV. Global Health Science Group, 2021)
Covid-19 pandemic has forced college students to study using online learning platforms. Therefore, this study focuses to examine the preferred media to facilitate e-learning and the students’ perception in using e-learning as a means of assessment. This study observes students from two private universities in Central Java namely Universitas Ngudi Waluyo and Universitas AKI, Indonesia, who have all taken English for Academic Purposes (EAP) lecture using YouTube and WhatsApp platform. 123 feedbacks were collected, and 17 students were chosen randomly to verify their answers of the questionnaires. The results of this study showed that e-learning using YouTube was preferable for students compared to using WhatsApp Group. The major problem of utilizing YouTube as e-learning was the slow and expensive data plan. The second result pointed out that most of the students or around 63% of the populations were neutral in terms of satisfaction level of online assessment. It could be inferred that this assessment method was acceptable for the students.